Características do livro didático de Língua Portuguesa na mediação da produção textual escrita - Rodrigues, Paulo Cezar (2007)
Since it is known that, as a rule, the school has not been successful in training proficient text writers; current research identifies the characteristics of the Portuguese Language textbook as a mediating factor in the teaching and learning process of texts within the teaching context. Textbooks in government schools in Maringá PR Brazil, in 2006, such as Português: linguagens (CEREJA & MAGALHÃES, 2002) and Português: leitura, produção, gramática (SARMENTO, 2002), were analyzed. Current qualitative, quantitative and interpretative research is based on the social-interactional theory of teaching, discussed in Applied Linguistics, and on researches and analyses on learning and teaching mediation of text writing production. Results of analyses in the context of textual production proposed by Cereja & Magalhães showed some of the mediator's traits. The latter were selected and classified as a) suggestions aiming at production; b) suggestions that specify the literary genre expected to be produced; c) suggestions with production socialization; d) suggestions that reveal the interlocutor. Sarmento's book, on the other hand, revealed that writing suggestions indicated different traits and, thus, a different classification: a) suggestions that do not take into consideration text production conditions; b) suggestions that specify and characterize textual genre to be produced; c) suggestions that do not reveal production aims; d) suggestions that do not specify nor characterize the required textual genre. Although writing suggestions in the two collections are different, results show that production conditions in Cereja & Magalhães's textbook indicate a mediating practice in the teaching and learning process of textual production within the teaching context. Actually, the textbook may be a mediator in the process when the theoretical and methodological supervision within the production conditions are taken into account in its suggestions on writing.